VALUATION OF THE TOURISM POTENTIALS FROM MARINE ECOSYSTEMS AROUND BACH LONG VI ISLAND IN HAI PHONG CITY - Lan, Tran Dinh; Chien, Hoang Thi; Huyen, Nguyen Thi Minh; Thu, Nguyen Thi; Quang, Bui Duc; Tuan, Ngo Minh (Vietnam Journal of Marine Science and Technology, 2015)
Bach Long Vi island is an offshore district in the centre of the Gulf of Tonkin in Vietnam and administratively belongs to Hai Phong city. The island surrounded by abundant marine ecosystems with high biodiversity is one of 16 marine protected areas approved by the Prime Minister of Vietnam on 26/5/2010 according to the Decision No.742/QD-TTg. Currently, in addition to the main service of economic activities as fishery logistics, Bach Long Vi island still remains the wild features with beautiful scenery, fresh air and the diversity of marine species that are suitable for the development of eco-tourism and resorts. Although tourism at present is not developed yet, its potentials are promising. Deploying zone travel cost method (ZTCM), tourism potentials based on ecosystem services of Bach Long Vi island were estimated at 5.4 billion VND (Vietnamese currency). The value can be much higher if the infrastructure of the island is improved and the island is accessible more easily. Tourism potential valuation and identification of the advantages of the island strongly support tourism planning in the future.